Civil Rights Act of 1871 - (:unkn) unknown (My University, 1871)
Discussion of the law and amendments in Congress used by the Court in DC v Heller to further instruct on the "well-known constitutional provision guaranteeing the right of the citizen to 'keep and bear arms,' and provides that whoever shall take away, by force or violence, r by threats and intimidation, the arms and weapons which any person may have for his defense, shall be deemed guilty of larceny of the same."
Keywords: GUARANTEED RIGHT